2003
DOI: 10.1080/15715124.2003.9635199
|View full text |Cite
|
Sign up to set email alerts
|

What kind of water models are needed for the implementation of the European water framework directive? Examples from France

Abstract: 2003) What kind of water models are needed for the implementation of the European water framework directive? ABSTRACTThe European Water Framework directive (WFD) promotes an integrated management approach, defines the river basin as the relevant management unit, and sets the objective of good ecological status for all waters in Europe before 2015. Based on research activities underway in France, this paper presents five examples of issues related to water modelling for the implementation of the WFD. The new co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 26 publications
(23 reference statements)
0
22
0
Order By: Relevance
“…Models can provide: an insight into the way rivers and catchments function; a framework for data analysis; a means of investigating problems; and, perhaps most usefully in the context of this paper, a way of evaluating alternative management strategies (Van der Molen, 1999;Wasson et al, 2003;Moll and Radach, 2003). However, using a model to support a water management function is not straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…Models can provide: an insight into the way rivers and catchments function; a framework for data analysis; a means of investigating problems; and, perhaps most usefully in the context of this paper, a way of evaluating alternative management strategies (Van der Molen, 1999;Wasson et al, 2003;Moll and Radach, 2003). However, using a model to support a water management function is not straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…The use of models as tools in the WFD context has been an issue of discussion and development as described e.g. by Wasson et al (2003) and Dørge and Windolf (2003). Moreover, Saloranta et al (2003) have suggested "benchmark criteria" against which the candidate models should be exposed to comprehensive testing in order to help water managers and other model users in choosing appropriate models for each WFD implementation purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Wasson et al (2003), Rekolainen et al (2003), andHeinz et al (2007) show that a set of different models pertaining to different areas of interest, such as the chemical or ecological status or the economy, is necessary for the successful implementation of the EU-WFD. These models, however, require reliable data for water quantities.…”
Section: Introductionmentioning
confidence: 99%